2016
DOI: 10.1097/jcp.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Separate and Combined Effects of Naltrexone and Extended-Release Alprazolam on the Reinforcing, Subject-Rated, and Cardiovascular Effects of Methamphetamine

Abstract: Opioid antagonists (e.g., naltrexone) and positive modulators of γ-aminobutyric acid type A (GABAA) receptors (e.g., alprazolam) each modestly attenuate the abuse-related effects of stimulants. A previous study demonstrated that acute pretreatment with the combination of naltrexone and alprazolam attenuated a greater number of the subject-rated effects of d-amphetamine than the constituent drugs alone. This study tested the hypothesis that maintenance on the combination of naltrexone and alprazolam XR would at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…Methamphetamine also produced a constellation of prototypical stimulant-like subjective effects indicative of abuse potential (e.g., Good Effects and Like Drug) and elevated systolic and diastolic blood pressure. These effects are consistent with the type and magnitude of effects typically observed following methamphetamine administration by various routes (e.g., Hart et al, 2001; Kirkpatrick et al, 2012; Marks et al, 2016; Pike et al, 2016; Stoops et al, 2015), but was not impacted by buspirone maintenance.…”
Section: Discussionsupporting
confidence: 85%
“…Methamphetamine also produced a constellation of prototypical stimulant-like subjective effects indicative of abuse potential (e.g., Good Effects and Like Drug) and elevated systolic and diastolic blood pressure. These effects are consistent with the type and magnitude of effects typically observed following methamphetamine administration by various routes (e.g., Hart et al, 2001; Kirkpatrick et al, 2012; Marks et al, 2016; Pike et al, 2016; Stoops et al, 2015), but was not impacted by buspirone maintenance.…”
Section: Discussionsupporting
confidence: 85%
“…. Lastly, naltrexone also attenuated the reinforcing effects of methamphetamine in a human laboratory study (Marks et al, 2016), although no effect was observed in another study with a similar experimental design (Stoops, Pike, Hays, Glaser, & Rush, 2015). Overall, these results suggest that naltrexone is less effective, less potent, and less reliable to block abuse-related effects of amphetamine than of -antagonists like morphine.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, studies in healthy as well as amphetamine-dependent subjects have reported that naltrexone maintenance decreased subjective effects of amphetamine (Jayaram-Lindstrom, Konstenius, et al, 2008; Jayaram-Lindstrom, Wennberg, Hurd, & Franck, 2004), and decreased metrics of amphetamine use in a placebo-controlled clinical trial (Jayaram-Lindstrom, Hammarberg, Beck, & Franck, 2008). Lastly, naltrexone also attenuated the reinforcing effects of methamphetamine in a human laboratory study (Marks et al, 2016), although no effect was observed in another study with a similar experimental design (Stoops, Pike, Hays, Glaser, & Rush, 2015). Overall, these results suggest that naltrexone is less effective, less potent, and less reliable to block abuse-related effects of amphetamine than of mu agonists like morphine.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, amphetamine’s own abuse liability is another undesirable amphetamine effect, and previous studies have suggested that naltrexone may attenuate abuse-related effects of amphetamine. For example, naltrexone decreased amphetamine self-administration in rhesus monkeys (Jimenez-Gomez et al, 2011), methamphetamine self-administration in a human laboratory study (Marks et al, 2016) and amphetamine use by patients meeting criteria for amphetamine dependence (Jayaram-Lindstrom et al, 2008). These findings suggest that combinations of amphetamine and naltrexone may have lower abuse liability than amphetamine alone.…”
Section: Discussionmentioning
confidence: 99%